2013
DOI: 10.1039/c3nr01464a
|View full text |Cite
|
Sign up to set email alerts
|

High-speed AFM for scanning the architecture of living cells

Abstract: We address the modelling of tip-cell membrane interactions under high speed atomic force microscopy. Using a home-made device with a scanning area of 100 × 100 μm(2), in situ imaging of living cells is successfully performed under loading rates from 1 to 50 Hz, intending to enable detailed descriptions of physiological processes in living samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In this study, it took 3 min to obtain one frame. With the high-speed AFM technology [59][60][61][62][63] , which is capable of imaging at 50-100 ms per frame under physiological conditions, more detailed dynamic observation could be possible.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, it took 3 min to obtain one frame. With the high-speed AFM technology [59][60][61][62][63] , which is capable of imaging at 50-100 ms per frame under physiological conditions, more detailed dynamic observation could be possible.…”
Section: Resultsmentioning
confidence: 99%
“…To enlarge the scan range, we built a fast AFM, where the X-Y motion is handled by a flexure stage that moves the sample while the Z motion is handled by a piezo stack moving the cantilever up and down. This homemade fast AFM has up to one hundred micrometers scan range and up to 50Hz line scan rate [6]. When in test processing, we found that with the most popular controller in AFM fast scanning, such as dynamic PI controller [7], model-based feedback controller [8] and inversion-based iterative controller [9], the Z scanner vibration can not be eliminated ideally.…”
Section: Fig1 Schematic Diagram Of Afm Operation[4]mentioning
confidence: 99%
“…To maintain controlled scanner motion at high scan rates, the design and control of mechanical scanners has played a crucial role in the development of HS-AFM systems [26,27]. Small, stiff scanners based on piezo tubes [2,3] or flexures optimized using finite element methods [4,6,18,28,[29][30][31] allow control to be maintained at high frequencies, but often at the expense of maximum scan size [32][33][34]. Notch filtering and model based feedback have allowed scanners to be driven at higher frequencies while mitigating the effects of resonant behavior [26,27,35,38,39], and non-raster scanning techniques such as Lissajous [40] and spiral scanning [41][42][43] allow control at high scan rates as the scanner drive signals do not contain components at higher harmonics of the scan frequency.…”
Section: Introductionmentioning
confidence: 99%